2020
DOI: 10.3844/jcssp.2020.1558.1569
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Techniques for Software Bug Prediction: A Systematic Review

Abstract: The goal of software bug prediction is to identify the software modules that will have the likelihood to get bugs by using some fundamental project resources before the real testing starts. Due to high cost in correcting the detected bugs, it is advisable to start predicting bugs at the early stage of development instead of at the testing phase. There are many techniques and approaches that can be used to build the prediction models, such as machine learning. This technique is widely used nowadays because it c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…The most widely used data sets in SDP are the Predictor Models in Software Engineering (PROMISE), and NASA Metrics Data Program (MDP)m according to Saharudin et al [ 6 ]. It was observed that 43.3% of each adopted data set was considered in research experiments, while in total usage, 86.6% was due to the open-source nature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most widely used data sets in SDP are the Predictor Models in Software Engineering (PROMISE), and NASA Metrics Data Program (MDP)m according to Saharudin et al [ 6 ]. It was observed that 43.3% of each adopted data set was considered in research experiments, while in total usage, 86.6% was due to the open-source nature.…”
Section: Methodsmentioning
confidence: 99%
“…Performance metrics are important indicators to measure and assess the quality of ML models. Saharudin et al [ 6 ] found that, for SDP, the most widely included types of numerical quantification measurements are Area Under Curve (AUC), based on the results of the Receiver Operating Characteristic (ROC) curve, hqving 56.7%, Recall, with 46.7%, F-Measure/F1-Measure, with 36.7%, Precision, with 30%, Accuracy, with 26.7%, and Other numerical measurements with 76.7%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metrics can also be classified based on development phase of software life cycle, into source code level metrics, detailed design level metrics or test level metrics. Objectoriented metrics are often used to assess the testability, maintainability or reusability of source code [20], [35]. Commonly dataset that used for software bug prediction domain is promise repository dataset.…”
Section: Software Metrics (Features) and Datasetsmentioning
confidence: 99%
“…During the life cycle's development phase, which also includes planning, deployment, design, testing, problem assessment, development, along with continuation, as well as software development life cycle models, machine learning techniques are used to anticipate software bugs. Machine learning techniques and statistical analysis may both be used to anticipate bugs (Saharudin, S.N et al, 2020) [3]. During the software development process, many approaches are employed to get better excellence.…”
Section: Introductionmentioning
confidence: 99%